(S)‐2‐[(N‐arylamino)methyl]pyrrolidines‐Based Phosphoramidite P, N‐Ligand Library for Asymmetric Metal‐Catalyzed Allylic Substitution and Conjugate 1, 4‐Addition. Issue 14 (6th September 2016) - Gavrilov, Konstantin N.; Mikhel, Igor S.; Chuchelkin, Ilya V.; Zheglov, Sergey V.; Gavrilov, Vladislav K.; Birin, Kirill P.; Tafeenko, Victor A.; Chernyshev, Vladimir V.; Goulioukina, Nataliya S.; Beletskaya, Irina P.
Abstract: A library of easy‐to‐prepare and modular chiral P, N ‐phosphoramidites based on [1, 1′‐biaryl]‐2, 2′‐diols and C 1 ‐symmetric 1, 2‐diamines has been designed and developed. The structures of the novel ligands have been elucidated by means of 2D‐NMR and confirmed in the solid state by X‐ray diffraction analysis. Stereoselectors of this type exhibited high enantioselectivities in Pd‐catalyzed allylic substitution reactions of ( E )‐1, 3‐diphenylallyl acetate with NaSO2 p Tol (up to 91 % ee ), CH2 (CO2 Me)2 (up to 89 % ee ), (C3 H7 )2 NH (up to 94 % ee ) and (EtO)2 P(O)CH2 NH2 as a novel nucleophile (up to 98 % ee ). Ee values of up to 88 % and 72 % have been obtained in the Pd‐catalyzed desymmetrization of N, N′ ‐ditosyl‐ meso ‐cyclopent‐4‐ene‐1, 3‐diol biscarbamate and in the Cu‐catalyzed 1, 4‐conjugate addition of diethylzinc to chalcone, respectively. The reactions of P, N ‐bidentate ligands with [Pd(Cod)Cl2 ] at molar ratios of L/M=1 and 2 have been studied using 1 H, 13 C, 13 C‐ 1 H HSQC, 13 C‐ 1 H HMBC, 1 H‐ 1 H COSY, 1 H‐ 1 H ROESY, DOSY and 31 P NMR spectroscopy as well as HR ESI mass spectrometry. Abstract : A library of easy‐to‐prepare and modular chiral P, N‐phosphoramidites based on [1, 1′‐biaryl]‐2, 2′‐diols and C1‐symmetric 1, 2‐diamines has been synthesized. These chiral inductors are solid, stable to air and are, therefore, easy to handle. In two simple steps, several ligand parameters have been tuned to maximize the catalyst performance. Novel ligands were employed in the asymmetric allylic substitution and desymmetrization (Pd‐catalyzed) as well as in the asymmetric conjugate addition (Cu‐catalyzed).